Modelación hidrológico con hec-hms y rs-minerve de la Cuenca del río Casacay – El Oro - Guaman Redrovan, Edwin Guillermo (Machala: Universidad Tëcnica de Machala, 2020)
The present degree work aims to determine the correlation that exists between the maximum flows calculated by HEC-HMS and RS-MINERVE, in order to verify the degree of reliability of these mathematical models, since they are currently the most widely used software for the elaboration of hydrological models in sub-watershed The data used were obtained from open databases available at national and international level, therefore a detailed investigation was performed to select the data that had the most influence on the sub-watershed under study. In addition, an arduous bibliographic investigation was carried out to select the calculation method that best suits the characteristic of the sub-watershed. Equally, for the geomorphological characterization, a geographic information system software was used to obtain the necessary parameters for hydrological modeling. In addition, an arduous bibliographic investigation was performed to select the calculation method that best suits the characteristic of the sub-watershed. On the other hand, for the geomorphological characterization, a geographic information system software was used to obtain the necessary parameters for hydrological modeling. Then the type of sub-model to be used was selected, where one of the most used in several investigations in the CN (Number of curves), which is based on the use and type of soil in the sub-watershed. Besides, we worked with precipitation histograms for several return periods. On the other hand, potential evapotranspiration was calculated for a year with the FAO calculator, whose input was obtained from a worldwide database, so it was defined for the study area. After obtaining the input data, the hydrological modeling programs chosen for the research were entered, data such as area, length of the watershed, CN, % of impermeability, delay time, histograms for several return periods, evapotranspiration, inter alia. While, to verify the degree of reliability of the maximum flows, the student t test was selected, since it is the most used for quantitative variables whose measurements are made to the same population in two different cases.
El presente trabajo de titulación tiene como objetivo determinar la correlación que existe entre los caudales máximos calculados por HEC-HMS y RS-MINERVE, para verificar el grado de confiabilidad de estos modelos matemáticos, ya que en actualidad son los softwares más empleadas para la elaboración de modelo hidrológicos en subcuencas. Los datos que se emplearon fueron obtenidos de base de datos abiertas que se encuentran disponibles a nivel nacional como a nivel internacional, por lo cual se realizó una minuciosa investigación para seleccionar los datos que más influencia tenían en la subcuenca de estudio. Además, se efectuó una ardua investigación bibliográfica para seleccionar el método de cálculo que más ajuste a la característica de la subcuenca. Por su parte, para la caracterización geomorfológica se empleó un software de sistema de información geográfica y así obtener los parámetros necesarios para la modelación hidrológica. Luego se seleccionó el tipo de submodelo a emplear, donde uno de los más utilizados en diversas investigaciones en el CN (Número de curvas), en cual se basa en el uso y tipo de suelo de la subcuenca. También, se trabajó con hietogramas de precipitación para varios periodos de retorno. Por otra parte, se calculó la evapotranspiración potencial para un año con la calculadora FAO, cuyos insumos de entrada se obtuvieron de una base de datos a nivel mundial, por lo cual se delimitó para el área de estudio. Después de obtener los datos de entrada, se procedió al ingreso en los programas de modelación hidrológica escogidos para la investigación, datos como área, longitud de la cuenca, CN, % de impermeabilidad, tiempo de retraso, hietogramas para varios períodos de retorno, evapotranspiración, entre otros. Mientras que, para verificar el grado de confiabilidad de los caudales máximos se seleccionó la prueba de T de student, al ser la más empleada para variables cuantitativos cuyas mediciones se la hacen a una misma población en dos casos diferentes.
Keywords: MODELO HIDROLÓGICO; CAUDAL MÁXIMO; EVAPOTRANSPIRACIÓN; RS-MINERVE